Factors influencing the negotiation of ethnic identity among 1.5 and second-generation Asian migrants: A mixed methods systematic review. (June 2021) - Dizon, Lovely; Selak, Vanessa; Ramalho, Rodrigo; Peiris-John, Roshini
Abstract: Introduction: Whilst positive ethnic identity is associated with higher self-esteem, prosocial tendencies and peer acceptance, it is inversely associated with depressive symptoms and drug use among ethnic minority individuals. Negotiating ethnic identity is particularly challenging for 1.5-and second-generation migrant populations, finding themselves positioned between host culture and culture of origin. To inform positive youth development policies and practices, this systematic literature review aimed to identify factors influencing the negotiation of ethnic identity for 1.5-and second-generation Asian migrants living in high-income countries. Methods: A mixed-methods systematic review was conducted of peer-reviewed literature in four databases: MEDLINE, EMBASE, PsychInfo and Scopus. Articles were screened by title, abstract and full text to ascertain whether they met the inclusion criteria. Quality of studies were assessed using MMAT Version 2011. Mixed-method thematic analysis was used to synthesis the data according to Bronfenbrenner's Ecological Model. Results: Forty-seven studies met the inclusion criteria. The review findings confirm a wide range of factors influencing the negotiation of ethnic identity from three systems in Bronfenbrenner's Ecological Model, most commonly from the macrosystem (e.g stereotyping), followed by microsystem (e.g family) and individual factors (e.g heritage language use). Conclusions: Results indicate negotiating ethnic identity can be challenging and difficult, where the culture/norms of country of origin and host country play a significant role. Positive youth development policies and practices need to reflect these wide range of factors. More research is needed in countries where data is not available to facilitate greater response to needs of this increasing population group.